2004
DOI: 10.1007/s00122-004-1848-9
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis and comparative genomics of herbage quality traits in perennial ryegrass (Lolium perenne L.)

Abstract: vivo dry matter digestibility (IVVDMD), neutral detergent fibre (NDF) content, estimated metabolisable energy (EstME) and water soluble

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 79 publications
3
58
1
Order By: Relevance
“…The coincidence of relatively large ADF and NDF content QTL effects in the centromere region of LG7a (Fig. 1), in both families, was particularly interesting because NDF, in vivo drymatter digestibility, and a cluster of lignin biosynthesis genes also co-localized in the centromeric region of LG7 in perennial ryegrass (Cogan et al 2005). Leymus LG7 is predicted be the conserved syntenic counterpart to perennial ryegrass LG7, which share the telomeric 6-SFT locus (Wei et al 2000;Lidgett et al 2002), and other syntenic crossspecies markers Wu et al 2003).…”
Section: Tcp2ns117 5hmentioning
confidence: 91%
See 2 more Smart Citations
“…The coincidence of relatively large ADF and NDF content QTL effects in the centromere region of LG7a (Fig. 1), in both families, was particularly interesting because NDF, in vivo drymatter digestibility, and a cluster of lignin biosynthesis genes also co-localized in the centromeric region of LG7 in perennial ryegrass (Cogan et al 2005). Leymus LG7 is predicted be the conserved syntenic counterpart to perennial ryegrass LG7, which share the telomeric 6-SFT locus (Wei et al 2000;Lidgett et al 2002), and other syntenic crossspecies markers Wu et al 2003).…”
Section: Tcp2ns117 5hmentioning
confidence: 91%
“…The NDF fraction includes cellulose, lignin, and hemicellulose; whereas the ADF fraction is composed mainly of cellulose and lignin without hemicellulose (Van Soest 1994). The genetic control of ADF and/or NDF content has been examined by QTL analysis in perennial ryegrass (Cogan et al 2005), maize (Krakowsky et al 2005(Krakowsky et al , 2006Lübberstedt et al 1997;Méchin et al 2001) and Arabidopsis (Barrière et al 2005). Crude protein and mineral content receive less attention by forage grass breeders, in part because soil fertility can have relatively large effect on these traits, because protein and mineral supplements are commonly used, and also because crude protein is often negatively correlated with yield (Casler and Vogel 1999;Casler 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…nutritional requirements, the qualities of the forage should be adjusted to fit that particular need (Brummer and Casler, 2009). Intergeneric hybridization between Lolium and fescue has been a common method to understand and improve the genetics underlying the forage quality (Naganowska et al, 2001;Cogan et al, 2005). In addition, applying approaches such as introgression mapping facilitated with either genomic in situ hybridization techniques or molecular markers, provide an additional set of powerful tools for forage quality improvements (Cardinal et al, 2003).…”
Section: Example 1: Gamete Selection For Crude Proteinmentioning
confidence: 99%
“…The fiber content can be quantified as neutral detergent fiber (NDF) and acid detergent fiber (ADF). Most crop research has found that these traits are controlled by quantitative trait loci (QTLs) (Cardinal et al, 2003;Cogan et al, 2005;Liu et al, 2012). Therefore, dissection of these QTLs will be helpful for the breeding of forage quality in sorghum-sudangrass hybrids.…”
Section: Introductionmentioning
confidence: 99%